Functions and Mechanisms of the Voltage-Gated Proton Channel Hv1 in Brain and Spinal Cord Injury - He, Junyun; Ritzel, Rodney M.; Wu, Junfang (Frontiers in Cellular Neuroscience, 2021)
The voltage-gated proton channel Hv1 is a newly discovered ion channel that is highly conserved among species. It is known that Hv1 is not only expressed in the immune system but also one of major ion channels expressed in tissue-resident microglia of the central nervous systems (CNS). One key role for Hv1 is its interaction with NADPH oxidase 2 (NOX2) to regulate reactive oxygen species and cytosolic pH. Emerging data suggest that Hv1 activity is disrupted in the injured CNS, and manipulations that ablate Hv1 expression or induce loss of function may provide neuroprotection in CNS injury models including stroke, traumatic brain injury, and spinal cord injury. Recent data demonstrating microglial Hv1-mediated signaling in the pathophysiology of CNS injury further supports the idea that Hv1 channel may function as a key mechanism in posttraumatic neuroinflammation and neurodegeneration. In this review, we summarize the main findings of Hv1, including its expression pattern, cellular mechanism, role in aging and animal models of CNS injury and disease pathology. We also discuss the potential of Hv1 as a therapeutic target for CNS injury.